Novel visualization of notational analysis data: the use of filters, 3D graphics and colours in visual identification of playing patterns - Radovan, M.; Kirkbride, A. N. (International Journal of Computer Science in Sport, 2005)
Inspired by the old adage, "a picture is worth more than a thousand words", this paper describes a novel approach to the visualization of complex cricket data. The objective is to present results to its target audience in a friendly and easily understandable manner. In cricket, the ability to take accurate and quick decision whilst the game is being played exerts a positive influence on the result of the match. This paper describes the use of 3-D visualization of data for decision support at International level of the sport. Our results demonstrate the importance of advancing the visualization of data and the need for pattern identification tools in order to gain a competitive advantage in cricket. Modern examples are presented of the current preferred method for displaying complex notational analysis data from elite level cricket.